Conjugation, characterization and toxicity of lipophosphoglycan-polyacrylic acid conjugate for vaccination against leishmaniasis - Topuzogullari, Murat; Koc, Rabia Cakir; Isoglu, Sevil Dincer; Bagirova, Melahat; Akdeste, Zeynep; Elcicek, Serhat; Allahverdiyev, Adil M. (Bmc, 2013)
Research on the conjugates of synthetic polyelectrolytes with antigenic molecules, such as proteins, peptides, or carbohydrates, is an attractive area due to their highly immunogenic character in comparison to classical adjuvants. For example, polyacrylic acid (PAA) is a weak polyelectrolyte and has been used in several biomedical applications such as immunological studies, drug delivery, and enzyme immobilization. However, to our knowledge, there are no studies that document immune-stimulant properties of PAA in Leishmania infection. Therefore, we aimed to develop a potential vaccine candidate against leishmaniasis by covalently conjugating PAA with an immunologically vital molecule of lipophosphoglycan (LPG) found in Leishmania parasites. In the study, LPG and PAA were conjugated by a multi-step procedure, and final products were analyzed with GPC and MALDI-TOF MS techniques. In cytotoxicity experiments, LPG-PAA conjugates did not indicate toxic effects on L929 and J774 murine macrophage cells. We assume that LPG-PAA conjugate can be a potential vaccine candidate, and will be immunologically characterized in further studies to prove its potential.
Keywords: Polymer; Vaccine; Delivery; Adjuvant; Leishmania; Conjugation